"Good to Say Out Loud": Researching Love across Class in Contemporary Australia. Issue 2 (3rd April 2022) - Butler, Rose; Vincent, Eve
ABSTRACT: In this article, we argue that romantic partnerships forged across class difference offer important insights into how class, privilege and inequality are experienced in Australia. We draw on new research into cross-class relationships to attend to the role that deeply enculturated class-based orientations play in the everyday lives of couples from different class backgrounds, while also exploring their entanglement with race, migration, gender and sexuality. We contend that documenting and understanding people's negotiations of such relationships through the lens of class difference has the potential to enhance broader understandings of what class is and means in contemporary Australia, a society long invested in egalitarianism as cultural mythology. In this article, we map the first stage of this interview-based research. We outline its scholarly basis and genesis before discussing two key sites of difference and negotiation within cross-class relationships—approaches to spending and saving money, and orientations to holidays, leisure and the use of time more broadly. At this early stage of the research, we describe ourselves as invited into explicit and richly complex conversations about class that have already begun for these couples, as a result of friction, affinities, earnest interest, amusement or desire.